Synthesize and characterization of cellulose nanofibrils to mitigate radon gas emanations from fabricated composite brick for heathy environment - Mocktar, Nurfarah Aini (2020)
Radon is a natural radioactive gas produced by U-238 decay series and mostly originated from rock, water, sand and soil. Brick that commonly consist of rock, water and sand becomes the main radon resources to human in indoor building environment. Radon gas can diffuse into respiration system during inhalation process and indirectly affects lung tissues by its energetic α particles that risk to lung cancer. Incorporating kenaf and oil palm cellulose nanofibrils (CNF) as liquid fillers into brick with certain ratios enable to mitigate radon gas emanations. This is due to reduction of radon resources utilization such as stone, sand and water as well as miniaturization of brick porosity. CNF were synthesis using combination of chemical pulping and ultrasonication methods before characterized with FESEM, XRD, XRF, BET and UTM. Surface morphology showed fibril diameter ranges were from 30-80 nm for kenaf and 20-60 nm for oil palm. Crystallinity index were 75.3% and 77% for kenaf and oil palm, respectively. Ten CNF composite bricks and one without CNF (control) were fabricated according to Malaysia Standard MS 7.6:1972 protocol. Five different amounts of CNF had been applied which were 40 ml, 80 ml, 120 ml, 160 ml and 200 ml while foaming agent was used to bind the mixtures. All bricks were dried in fume hood at room temperature for 48 hours. Radon Sentinel Monitor model 1030 was used to determine the radon concentrations, humidity, pressure and temperature for each brick within 10 consecutive days in a close-space of prototype perspex room. Control brick gave highest radon concentration of 3.77 pCi/L whereas 40 ml CNF composite bricks from kenaf and oil palm gave 1.4 pCi/L and 0.93 pCi/L, respectively. 40 mlCNF from oil palm was the optimum amount to mitigate radon emanation with ~75% reduction. For physical testing, control brick was cracked at force 39013 N whereas 50458 N for 40 ml kenaf and 42160 N for 40 ml oil palm CNF bricks. Meanwhile, surface area porosity for control brick was 3.4473 m2/g whereas 6.4449 m2/g for 40 ml kenaf and 4.9025 m2/g for oil palm CNF bricks with pore size 2.92 nm, 0.347 nm and 2.27 nm for each. Application of small amount CNF for both plants also reduced the radon emanations and increased the physical strength of the bricks. In this study, 40 ml CNF of both kenaf and oil palm were the optimum ratios in mitigating radon emanations, miniaturization the porosity and increased the physical strength of the fabricated composite bricks.